Evaluación de camote morado (Ipomoea batatas Lam) combinado con Lactobacillus plantarum como alternativa alimenticia de cerdos en etapa crecimiento-engorde - Falcones Farfan, Carmen Leticia (2023)
The present investigation was carried out in the facilities of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, in the area of the Unit of Integration and Linkage Hato Porcino, with the objective of evaluating the inclusion of purple sweet potato (Ipomoea batatas Lam) combined with Lactobacillus plantarum during the growth-fattening stage in pigs. There were 24 experimental units which were distributed in four treatments of five piglets plus the control; with two levels of purple sweet potato flour of 10 and 15% plus 20 and 40 ml of L.plantarum; the data is analyzed by means of the statistical software InfoStat. The results for the variables weekly weight (PS), weekly weight gain (GDPS), feed conversion (CA) did not reflect significant differences (P>0.05) in the treatments; It is highlighted that the results are similar for the variables in the final week; for the PS, an average was obtained in T4 of 50.51 and T0 with 53.29; Likewise, the GDPS showed that in T1 it was 5.66, being higher than T0 with 5.22; In the same way, the CA achieved that the T2 was 3.43 and the T0 with 3.14; In the health aspect, the higher the concentration of Lactobacillus plantarum, the lower the presence of parasite colonies, since this helps to improve the balance of the intestinal microbiota. It is concluded that the purple sweet potato combined with Lactobacillus plantarum is a viable alternative for food for the small and medium producer.